Diamorphine or morphine for ischaemic cardiac chest pain. Issue 3 (1st May 2003) - Halford, Steve; Simpson, H
Abstract : A short cut review was carried out to establish whether morphine is better than diamorphine at allieviating chest pain after an acute myocardial infarction. Altogether 66 papers were found using the reported search, of which one presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of this best paper are tabulated. A clinical bottom line is stated.